Defining Illegal Forest Activities and Illegal Logging - Cerutti, Paolo Omar (2016)
This report presents the results of the fifth global scientific assessment undertaken by the GFEP initiative. The report set out to gain deeper understanding of the meaning of illegal logging and related timber trade, its scale, drivers and consequences. It provides a structured synthesis of available scientific and expert knowledge on illegal logging and associated timber trade while adding to existing studies and reports by sharing new insights, including a criminology perspective and new information about timber and timber product trade flows as well as exploring future policy options and governance responses. This assessment report and the accompanying policy brief provide an authoritative source of information for policymakers and stakeholders involved in the fight against illegal logging and associated timber trade, in order to support effective action in tackling this pressing global problem